1982
DOI: 10.1002/1097-0142(19820715)50:2<360::aid-cncr2820500233>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of hereditary cancer of the breast and colon

Abstract: The natural history of 106 patients from eighteen families manifesting hereditary breast cancer syndromes, and 117 affected patients from twenty families manifesting nonpolyposis hereditary colon cancer were evaluated. Findings were compared with the American College of Surgeons (ACS) long‐term audits for breast and colon cancer respectively. The cardinal features of hereditary cancer were observed within the study group, including: (1) a significant younger age of onset (49 years, breast; 46 years, colon); (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
1
5

Year Published

1984
1984
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(41 citation statements)
references
References 12 publications
4
31
1
5
Order By: Relevance
“…It has been suggested that familial breast cancer has a better prognosis than sporadic (Albano et al, 1982). Among the present 6 cases, 2 are still alive 20 years and 19 years respectively after diagnosis; a third patient is alive nearly 3 years after diagnosis; and a fourth patient died after 72 years.…”
Section: Discussionmentioning
confidence: 64%
“…It has been suggested that familial breast cancer has a better prognosis than sporadic (Albano et al, 1982). Among the present 6 cases, 2 are still alive 20 years and 19 years respectively after diagnosis; a third patient is alive nearly 3 years after diagnosis; and a fourth patient died after 72 years.…”
Section: Discussionmentioning
confidence: 64%
“…Selection bias and the possible effects of enhanced diagnostic or preventive screening have often hampered efforts to confirm the hypothesis of a more favorable prognosis for colorectal cancer in HNPCC and FAP (Albano et al, 1982;Bertario et al, 1994;Bulow et al, 1995;Jarvinen et al, 1995). The aim of our study was to compare the prognosis of colorectal cancer in HNPCC, FAP and sporadiccolorectal-carcinoma patients.…”
mentioning
confidence: 99%
“…In contrast, there are few studies that have examined the association between breast cancer histopathology and a family history of breast cancer (Rosen et al, 1982;Claus et al, 1993; Fukutomi et al, 1993). There are, however, several anecdotal reports of improved survival rates in patients with a family history of breast cancer (Lynch et al, 1981;Albano et al, 1982). The few studies carried out since the identification of the BRCAJ gene have reported a more favourable prognosis for patients from BRCAI-linked breast/ovarian cancer families (Malone et al, 1996;Marcus et al, 1996;Rubin et al, 1996).…”
mentioning
confidence: 99%